2020
DOI: 10.1002/jeab.591
|View full text |Cite
|
Sign up to set email alerts
|

Choice for reinforced behavioral variability in children with autism spectrum disorder

Abstract: Although individuals with autism spectrum disorder (ASD) tend to behave repetitively, certain reinforcement contingencies (e.g., lag schedules) can be used to increase behavioral variability. In a lag schedule, reinforcers only follow responses that differ from recent responses. The present study was designed to promote variable play behavior in preschoolers with ASD interacting with playsets and figurines and to assess preference for variability and repetition contingencies. Data have shown a preference for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…For example, children with autism spectrum disorder (ASD) tend to behave overly repetitively, even when it would be beneficial to respond variably (American Psychological Association [APA], 2013). Because variability is adaptive in many contexts, increasing behavioral variability is often a treatment goal for individuals with ASD (see Galizio et al, 2020). Therefore, it would be useful to know whether reinforced behavioral variability would reoccur in the face of treatment infidelity or other challenges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children with autism spectrum disorder (ASD) tend to behave overly repetitively, even when it would be beneficial to respond variably (American Psychological Association [APA], 2013). Because variability is adaptive in many contexts, increasing behavioral variability is often a treatment goal for individuals with ASD (see Galizio et al, 2020). Therefore, it would be useful to know whether reinforced behavioral variability would reoccur in the face of treatment infidelity or other challenges.…”
mentioning
confidence: 99%
“…Further, organisms can learn to behave variably in one context and repetitively in another (e.g., Denney & Neuringer, 1998; Ward et al, 2008). Reinforced behavioral variability may play an important role in processes such as problem solving and creativity (Grunow & Neuringer, 2002) and has been demonstrated across a number of species, including pigeons (e.g., Doughty & Galizio, 2015; Machado, 1997; Odum et al, 2006; Page & Neuringer, 1985), rats (e.g., Cohen et al, 1990; Neuringer, 1991), typically developing adults (e.g., Neuringer, 1986; Ross & Neuringer, 2002), and individuals with autism (e.g., Galizio et al, 2020), indicating that it is a general behavioral phenomenon.…”
mentioning
confidence: 99%
“…The past decade witnessed a tendency for coupled/comparative studies, in which the results obtained from avian and human subjects were jointly analyzed. Most of these studies tackled different behavioral features of diagnostic or therapeutic significance of ASD ( Koshiba et al, 2016 ; Kelley et al, 2017 ; Galizio et al, 2020 ; Shvarts et al, 2020 ). In addition, molecular neuroanatomical studies, carried out on multiple species, including man, have also been reported, e.g., for the comparative localization of FMRP (see above) in the auditory system ( Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some applications of reinforced behavioral variability principles have already been implemented in individuals with ASD (Rodriguez & Thompson, 2015; Wolfe et al, 2014). For example, children with ASD can learn to vary verbal and play behaviors using lag schedules (Brodhead et al, 2016; Galizio et al, 2020). There is convincing evidence that variability can be increased using reinforcement in both humans and nonhumans.…”
mentioning
confidence: 99%